Peran Sistem Informasi Aplikasi Go Online (GOOL) Dalam Meningkatkan Efisiensi Kerja Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kota Probolinggo - Mastina Maksin; Renny Candradewi Puspitarini; Lovita Adelia Citra; Anila Ifana; Dwi Ayu Wulandari; Lintang Dwi Sagita Cahyani (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this research is to find out how information systems are made to improve the work efficiency of Dukcapil employees of Probolinggo City. Population Administration Service is a forum to serve the community in taking care of personal and public identity papers. Population administration services need to be improved in order to follow the rapid development of information technology. In addition, the government is also determined to always develop something new in facilitating public access. In this era of globalization, people are more dominant in choosing instant administrative services. Now the Probolinggo City Population and Civil Registration Office has created a web application, in addition to making it easier for the community to also to improve the work efficiency of employees, with this it can be assessed on the work achievements of employees who have created online-based public services, so that the people of Probolinggo City continue to follow the existing information technology developments, besides that improving public services in Probolinggo City itself. This can minimize discrimination, as well as lack of effectiveness in employee performance. The method used in this research is a descriptive qualitative method in describing the implementation of information technology in public services in the field of population administration online by using the Go Online application (GOOL). In addition, it is also supported by secondary data obtained from library results. The findings of this study are how to use the application, what things can improve employee work efficiency and what problems often occur in this service